2020
DOI: 10.3390/en13246554
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning Methods to Select Potential Depot Locations for the Supply Chain of Biomass Co-Firing

Abstract: Coal is the second-largest source for electricity generation in the United States. However, the burning of coal produces dangerous gas emissions, such as carbon dioxide and Green House Gas (GHG) emissions. One alternative to decrease these emissions is biomass co-firing. To establish biomass as a viable option, the optimization of the biomass supply chain (BSC) is essential. Although most of the research conducted has focused on optimization models, the purpose of this paper is to incorporate machine-learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Jiang et al (2019) used logistic regression for predictions of aflatoxin in grain at a postharvest stage, providing a base for guaranteeing the safety of stored grain by providing early warning on contaminant problems emerging while storing the product. Goettsch et al (2020) used a multi-layer perceptron algorithm in a mathematical modeling problem where the aim was to decrease gas emissions by optimizing the biomass supply chain. There are novel research studies for using supervised machine learning methods in production planning.…”
Section: Comparing Supervised Unsupervised and Reinforcement Machine Learning Algorithmsmentioning
confidence: 99%
“…Jiang et al (2019) used logistic regression for predictions of aflatoxin in grain at a postharvest stage, providing a base for guaranteeing the safety of stored grain by providing early warning on contaminant problems emerging while storing the product. Goettsch et al (2020) used a multi-layer perceptron algorithm in a mathematical modeling problem where the aim was to decrease gas emissions by optimizing the biomass supply chain. There are novel research studies for using supervised machine learning methods in production planning.…”
Section: Comparing Supervised Unsupervised and Reinforcement Machine Learning Algorithmsmentioning
confidence: 99%
“… 35 , 36 Based on various ML algorithms, most studies focus on supplier selection, 37 39 whereas others focus on supply chain risk management. 40 Moreover, few authors have focused on inventory management, 41 and few authors center on demand forecasting. 42 These studies fully revealed the positive significance of ML in SCM.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these challenges, machine learning has gained traction as a tool to reduce the computational burden of complex optimization models [5], [6]. Goettsch et al utilized machine learning to reduce the number of potential depot locations for biomass cofiring [7].…”
mentioning
confidence: 99%